2010
DOI: 10.1111/j.1745-4530.2009.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

NONLINEAR ESTIMATION OF RESPIRATORY DYNAMICS OF FRESH‐CUT SPINACH (SPINACIA OLERACEA) BASED ON ENZYME KINETICS

Abstract: The respiratory behavior of fresh‐cut spinach under different temperatures and gas conditions was evaluated to develop an integrated respiration model taking into account the temperature dependence of enzyme kinetics parameters. The dependence of respiration rate on the O2 and CO2 concentrations has been described assuming the enzyme kinetics model for combined type of inhibition caused by CO2. The respiration model parameters under the specified environmental conditions of 10, 15, 20C and 75% relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
5
18
0
3
Order By: Relevance
“…It indicated that the low temperature could effective resist respiration rates of mung bean sprouts. It appears to be in agreement with the observation of Kaur et al (Kaur et al 2011). The O 2 consumption rate of fresh-cut spinach decreased by 54.24% by decreasing the temperature from 20 to 10C.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It indicated that the low temperature could effective resist respiration rates of mung bean sprouts. It appears to be in agreement with the observation of Kaur et al (Kaur et al 2011). The O 2 consumption rate of fresh-cut spinach decreased by 54.24% by decreasing the temperature from 20 to 10C.…”
Section: Resultssupporting
confidence: 93%
“…It appears to be in agreement with the observation of Kaur et al (Kaur et al . ). The O 2 consumption rate of fresh‐cut spinach decreased by 54.24% by decreasing the temperature from 20 to 10C.…”
Section: Resultsmentioning
confidence: 97%
“…The dependence of respiration rate on the headspace O 2 and CO 2 concentrations has been described assuming the enzyme kinetics model for combined type of inhibition proposed by Peppelenbos and Van't Leven (1996). The effect of surrounding temperature on the respiratory parameters has been evaluated using the Arrhenius relationship (Fonseca et al 2002;Benkeblia 2004;Charles et al 2005;Kaur et al 2011). The changes in the respiratory parameters on account of minimal processing have also been discussed.…”
Section: Resultsmentioning
confidence: 99%
“…A two to three fold increase in biological reactions has been reported for every 10°C rise in temperature within the range of temperatures normally encountered in the distribution and marketing chain. Arrhenius law has been widely used to describe temperature dependence of respiration rates (Fonseca et al 2002;Kaur et al 2011;Benkeblia 2004;Charles et al 2005). All the parameters of enzyme kinetics model were evaluated using Arrhenius law [ k ¼ Ae ÀEa RT ] to study the effect of storage temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Most respiration rate models have been oriented towards either one or two out of the three functions of time, temperature and gas composition. The Michaelis-Menten type equations (uncompetitive, noncompetitive, or uncompetitive/competitive) based on CO 2 inhibitory effect (Lee et al 1991;Peppelenbos and Leven 1996;Del Nobile et al 2006;Rocculi et al 2006;Bhande et al 2008), and the Arrhenius-type equations, which describe temperature as a function of respiration (Jacxsens et al 2000;Kaur et al 2010;Uchino et al 2004;Torrieri et al 2010), have been widely reported for respiration rate of fresh produce as a function of both temperature and gas composition. A major limitation of respiration rate modelling is of the lack of adequate respiratory data information.…”
Section: Produce Physiology and Mathematical Predictionsmentioning
confidence: 99%